2017
DOI: 10.1038/s41598-017-07860-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safe use and dietary risk of beta-cypermethrin, pyriproxyfen, avermectin, diflubenzuron and chlorothalonil in button mushroom

Abstract: In this study, the residues of beta-cypermethrin, pyriproxyfen, avermectin, diflubenzuron and chlorothalonil in button mushrooms were investigated. The dietary risks of ingesting button mushrooms that have had these pesticides applied by two different methods under normal plant conditions were evaluated. The dissipation of these pesticides into the soil was also studied. According to the maximum residue limits (MRLs) and acceptable daily intakes (ADIs), the final residues of beta-cypermethrin, pyriproxyfen, av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Despite the economic importance and the considerable losses caused by the pathogen H. perniciosus , little is known about the genetic and pathogenic mechanisms underlying the interaction between H. perniciosus and the fungal host. Previous research has focused on the disease occurrence, genetic diversity, pathogenesis, pathogenicity, identification of disease resistance, and integrated control and management of the disease [3,4,7,8,9,10]. Genomic analysis of pathogens is also one of the most effective ways to obtain a full understanding of fungal pathogenesis at the molecular level [10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the economic importance and the considerable losses caused by the pathogen H. perniciosus , little is known about the genetic and pathogenic mechanisms underlying the interaction between H. perniciosus and the fungal host. Previous research has focused on the disease occurrence, genetic diversity, pathogenesis, pathogenicity, identification of disease resistance, and integrated control and management of the disease [3,4,7,8,9,10]. Genomic analysis of pathogens is also one of the most effective ways to obtain a full understanding of fungal pathogenesis at the molecular level [10].…”
Section: Introductionmentioning
confidence: 99%
“…A similar study was performed by Du et al [46] with button mushrooms (Agaricus bisporus) growing on a substrate including wheat straw (78%), chicken manure (20%) and slaked lime (2%). In the substrate, the residue of pyriproxyfen (10% SC) was <0.1 mg/kg three days after application.…”
Section: Dissipationmentioning
confidence: 70%
“…To date, several methods have been used to determine the residue behaviors of pyriproxyfen in tomato, 20 pepper, 21 citrus, 22 peach, 23 grape 24 and mushroom, 25,26 and residues have been reported in different fruits and vegetables. [27][28][29][30][31] However, no studies have reported the degradation behavior of pyriproxyfen and its metabolites in tea.…”
Section: Introductionmentioning
confidence: 99%